Incorporation of ophiobolin a into novel chemoembolization particles for cancer cell treatment - Morrison, R; Gardiner, C; Evidente, A; Kiss, R; Townley, H (Springer Verlag, 2014)
Purpose To design and synthesize chemoembolization particles for the delivery of Ophiobolin A (OphA), a promising fungal-derived chemotherapeutic, directly at the tumour location. To investigate cell death mechanism of OphA on a Rhabdomyosarcoma cancer (RD) cell line. Rhabdomyosarcoma is the most common soft tissue sarcoma in children; with a 5-year survival rate of between 30 and 65%. Methods Multimodal chemoembolization particles were prepared by sintering mesoporous silica nanoparticles, prepared by the sol-gel method, onto the surface of polystyrene microspheres, prepared by suspension copolymerisation. The chemoembolization particles were subsequently loaded with OphA. The effects of OphA in vitro were characterised by flow cytometry and nanoparticle tracking analysis (NanoSight). Results High loading of OphA onto the chemoembolization particles was achieved. The subsequent release of OphA onto RD cells in culture showed a 70% reduction in cell viability. OphA caused RD cells to round up and their membrane to bleb and caused cell death via apoptosis. OphA caused both an increase in the number of microvesicles produced and an increase in DNA content within these microvesicles. Conclusions The prepared chemoembolization particles showed good efficacy against RD cells in culture.